2022
DOI: 10.3390/biomedicines10082000
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adiponectin in the Resolution of Male-Obesity-Associated Secondary Hypogonadism after Metabolic Surgery and Its Impact on Cardiovascular Risk

Abstract: Male-obesity-associated secondary hypogonadism (MOSH) is a very prevalent entity that may resolve after marked weight loss. Adiponectin (APN) is an adipokine with anti-inflammatory properties that regulates metabolism. Low-circulating APN is associated with obesity, diabetes, and cardiovascular risk, along with circulating testosterone. We aimed to evaluate APN changes in men with MOSH (low circulating free testosterone (FT) with low or normal gonadotropins) and without it after metabolic surgery. We look for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…One study showed that cIMT was negatively correlated with TT in 115 men younger than 70 years without a history of cardiovascular events [ 24 ], but other studies failed to show an association of circulating androgens with cIMT [ 25 , 26 ]. We have recently shown that those men with hypogonadism who achieve a complete normalization of testosterone after metabolic surgery experience a significant decrease in cIMT compared to those who remain hypogonadal [ 23 ]. It seems that the increase in circulating testosterone after metabolic surgery is the result of weight loss and the amelioration of insulin and leptin resistance [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that cIMT was negatively correlated with TT in 115 men younger than 70 years without a history of cardiovascular events [ 24 ], but other studies failed to show an association of circulating androgens with cIMT [ 25 , 26 ]. We have recently shown that those men with hypogonadism who achieve a complete normalization of testosterone after metabolic surgery experience a significant decrease in cIMT compared to those who remain hypogonadal [ 23 ]. It seems that the increase in circulating testosterone after metabolic surgery is the result of weight loss and the amelioration of insulin and leptin resistance [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding men who submitted to metabolic surgery, more than half may present secondary hypogonadism, and its resolution can be achieved in most of them after surgery [ 22 ]. We have previously shown that the decrease in cIMT correlated with the increase in total testosterone and weight loss after metabolic surgery in men [ 10 , 23 ].…”
Section: Introductionmentioning
confidence: 99%